Growth and productivity of Solanum lycopersicum L. on soil amended with vermicompost subjected to different storage treatments - Mantilla, Krisha Marie M. (Department of Biology and Environmental Science, College of Science, University of the Philippines Cebu, 2022)
The benefits of vermicompost in promoting sustainable agriculture by means of optimizing plant growth and yield is widely documented. However, vermicompost quality is reported to deteriorate during storage thereby raising questions regarding the efficacy of stored vermicompost when used as biofertilizer for plants. IN this study, I conducted a pot experiment in a randomized complete block design to evaluate the growth and productivity of tomato plant Solanum lycopersicum L. in response to amendment of vermicompost subjected to different storage conditions: in (a) airtight, (b) holed, and (c) open polyethylene bags. This was to determine the appropriate storage treatment with which the efficacy of vermicompost as biofertilizer is prolonged despite the imminent deterioration of vermicompost quality with time. Mean plant growth and yield parameters between treatments were compared using the two-way ANOVA without interaction. I found that treatment of stored vermicompost significantly improved growth rate, stem height, main stem diameter, average leaf area, number of fruits per plat and average fruit weight and diameter. However, the effect of the differently stored vermicompost on the growth and productivity of S. lycopersicum did not significantly differ suggesting that regardless of the storage type, vermicompost stored for 50 days could still be rendered as a variable biofertilizer. I recommend that similar studies must conducted in the future but with a longer storage period for vermicompost and growth period for the study species.